Institutional Collaboration on the Lake of Bakuok in Sustainable Management - Afrizal Afrizal; Mayarni Mayarni; Mimin Sundari Nasution (Indonesian Association for Public Administration (IAPA), 2019)
Lake Bakuok is a conservation area and traditional indigenous Lake or prohibition hole that has culture-based fishing activities, we can see this with the tradition of fishing together using nets that have become tourist destinations in Kampar Regency, Riau Province, in regional languages locally called